Sales Information System On The Liemo'S Trophy Cup Using Apriori Algorithm - Afifah Nur Aini; Sri Eniyati (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2022)
The Liemo'S Trophy trophy shop was pioneered in early 1996 until 2022. Currently, we can see the rapid development of business in the field of trophy sales, with many trophy shops that have been opened. Therefore Liemo'S Trophy trophy shop must take steps forward to achieve high sales strategy by its competitors. The rapid development of information technology and information systems in the era of globalization, makes information can be obtained easily and quickly, one of which is the business field in the era of globalization, there are many information systems that provide convenience and good service for users of information system services, because information systems is the key in the development of an information technology. Like the Liemo's Trophy Cup shop, it sells various kinds of trophies, medals, plaques, and sells spare parts and trophy needs including figures and various other accessories, but this shop still processes data manually so that sellers will find it difficult to manage sales data. Creating a sales information system using a web-based Apriori Algorithm is expected to get a sales strategy and can be widely used in the sales process to increase the marketing of goods widely through online sites.